2021
DOI: 10.1111/ejh.13674
|View full text |Cite
|
Sign up to set email alerts
|

TRough versus AUC Monitoring of cyclosporine: A randomized comparison of adverse drug reactions in adult allogeneic stem cell recipients (TRAM study)

Abstract: Objective To investigate the incidence and severity of adverse drug reactions of cyclosporine using AUC‐targeted therapeutic drug monitoring (TDM) compared to trough level (Ctrough)‐targeted TDM in adult allogeneic stem cell recipients. Methods Blind, monocenter, intervention study. Subjects were 1:1 randomized into either an AUC group or a Ctrough group. Adverse drug reactions were accessed two and four weeks after start of treatment. Results Forty patients were included, resulting in 15 evaluable subjects (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…For this purpose, professional work groups involved in different analytic and evaluating phases of the TDM procedures have regularly aimed at providing guidelines for improved immunosuppression, such as the report of the European consensus conference in 2009 on opportunities to optimize tacrolimus therapy in solid organ transplantation [ 20 ], the Second Consensus Report Therapeutic Drug Monitoring of Tacrolimus-Personalized Therapy, recommendations of the International Association of Therapeutic Drug Monitoring and Clinical Toxicology (IATDMCT) on the therapeutic drug monitoring of tacrolimus [ 21 ]. In the search for optimal target TDM levels, the TRAM study found no difference In CsA-induced toxicity with the area under the curve (AUC)-based TDM versus the trough-based TDM, although target values were achieved earlier and maintained more consistently in the AUC group [ 22 ]. In addition, inter- and intrapatient variabilities in pharmacokinetics (PK) have been quantified for population PK models to be used to predict the optimal dose of a drug in an individual patient.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, professional work groups involved in different analytic and evaluating phases of the TDM procedures have regularly aimed at providing guidelines for improved immunosuppression, such as the report of the European consensus conference in 2009 on opportunities to optimize tacrolimus therapy in solid organ transplantation [ 20 ], the Second Consensus Report Therapeutic Drug Monitoring of Tacrolimus-Personalized Therapy, recommendations of the International Association of Therapeutic Drug Monitoring and Clinical Toxicology (IATDMCT) on the therapeutic drug monitoring of tacrolimus [ 21 ]. In the search for optimal target TDM levels, the TRAM study found no difference In CsA-induced toxicity with the area under the curve (AUC)-based TDM versus the trough-based TDM, although target values were achieved earlier and maintained more consistently in the AUC group [ 22 ]. In addition, inter- and intrapatient variabilities in pharmacokinetics (PK) have been quantified for population PK models to be used to predict the optimal dose of a drug in an individual patient.…”
Section: Discussionmentioning
confidence: 99%